Economic Loss Analisys Pasien Rawat Inap Usia Produktif : (Studi Pada RSUD Prof.Dr.H.Aloei Saboe Kota Gorontalo) - Syawaluddin Syawaluddin (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
This study aims to determine the level of economic loss of inpatients of productive age and to analyze the loss calculation and classification of the most dominant types of disease in this case. This research data is in the form of primary and secondary data obtained by interviews, interviews and documentation, then the overall data is carried out descriptive analysis on each research variable. The results of this study indicate that: The average length of treatment for the 5 main diseases which are the object of the study, ie ranging from 5 to 8 days of treatment depending on the type of disease and level of care. The total economic loss in direct financing is IDR 6,766,806,370 for 5 major diseases in the period January 2018 to November 2019. The total economic loss in indirect financing is IDR 2,115,597,239 for 5 major diseases from January 2018 to November 2019. Total losses (economic loss) against lost opportunities or lost income due to loss of productive time amounted to IDR 253,692,000 in 5 major diseases for the period January 2018 to November 2019. Total costs incurred by inpatients (economic loss) amounting to Rp. 9,136,095,609 during the period January 2018 to November 2019 for 5 major diseases in patients of productive age.